SECURED DECENTRALIZED CONFIDENTIAL DATA DISTRIBUTED ACROSS A DISRUPTION-TOLERANT MILITARY NETWORK. WITH THE ALGORITHM MD5 AND 3DES - RHATAVAL AVADHUT DHONDIRAM; PROF.DR.K.R.DESAI (International Journal of Innovations in Engineering Research and Technology, 2021)
Confidential information or data reliably through the operation of external storage nodes. Some of the most difficult problems in this scenario are the application of approval policies and updating the policies for secure data recovery. The attribute-based encryption of cipher textpolicy is a promising cryptographic solution for access control issues. However, the problem of using CP -ABE in the decentralized tolerance network poses some challenges of security and privacy in terms of the revocation of attributes, the blocking of keys and the coordination of attributes of different authorities. We propose a secure scheme of data rescue, by using the idea of decentralized, tolerant networks in which multiple key management administrators independently manage their attributes. We show how to use the proposed mechanism to safely and effectively manage confidential information or data distributed in the gust of the military network.